ANALISIS KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK FASE E SMA NEGERI 3 TANJUNG RAJA PADA MATERI PERUBAHAN LINGKUNGAN - Ida Fitriani; Sri Wardhani; Marlina Ummas Genisa; Meli Astriani (Bioedukasi Jurnal Pendidikan Biologi, 2024)
Critical thinking skills are important for students to have when facing the challenges of the 21st century. This skill can help students overcome problems in the real world, one of which is the problem of environmental change. This research is qualitative with a descriptive approach, to evaluate the critical thinking abilities of students in class X SMA Negeri 3 Tanjung Raja on environmental change material. The number of research subjects was thirty. The critical thinking ability test consists of five questions that refer to five indicators: providing simple basic explanations, building basic skills, drawing conclusions, providing further explanations, and organizing strategies and tactics. The results showed that participants had a low level of critical thinking, especially in terms of indicators of concluding.